INTEGRATION OF WEBBLOGS AS DIGITAL PORTFOLIOS: INNOVATION IN PHOTOGRAPHY LEARNING MEDIA IN THE DIGITAL LITERACY ERA - Karyadi, Bambang (EDUCATE : Jurnal Teknologi Pendidikan, 2026)
This study aims to analyze student responses to the integration of weblogs as digital portfolios in the Photography course within the Educational Technology Undergraduate Program, Faculty of Teacher Training and Education, Ibn Khaldun University, Bogor. Inthe digital literacy era, the ability to manage work professionally has become a crucial competence for educational technologists. This research employed a descriptive quantitative method with a sample of 50 students drawn from a population of 98 (Academic Year 2024-2025). Data were collected using a 4-point Likert scale questionnaire instrument covering five key indicators. The results indicate that the integration of weblogs is considered highly effective, with an overall mean score of 3.61 (Strongly Agree). The highest scores were achieved in the indicators of Archive Management (3.72) and Career Relevance (3.70), indicating that students perceive digital portfolios as both a secure storage tool for their work and a future professional investment. Nevertheless, the Ease of Use indicator (3.46) suggests a need for additional technical guidance regarding blog design. The conclusion of this study confirms that weblogs are effectively utilized as an innovative photography learning medium capable of enhancing students’ digital literacy and personal branding.